Flood risk management in Europe: the EU 'Floods' directive and a case study of Ireland. Issue 3 (3rd July 2018) - Adamson, Mark
ABSTRACT: The 'Floods' Directive sets out a basic framework for good practice in flood risk management comprising a screening exercise, the Preliminary Flood Risk Assessment, to identify the Areas of Potentially Significant Flood Risk (APSFRs), and then the preparation of flood maps for these areas, and the preparation of flood risk management plans to set out measures to address the flood risk in the APSFRs. The Directive provides significant subsidiarity to allow the Member States to determine how best to apply the framework in the most appropriate way given the legacy and context of flood risk management within their own country. As a result, the Member States have taken a range of diverse approaches in applying the requirements of the Directive. In Ireland, a major national programme of analysis has delivered on the requirements of the Directive that has involved the development of a range of new approaches and methodologies. These have included bespoke methods of broad-scale risk assessment, and the development of weighted objectives reflecting societal values for use in a Multi-Criteria Analysis to determine the most appropriate flood risk management measures for each community at risk. This paper reflects on some of the issues and challenges faced in implementing the 'Floods' Directive across the EU, and outlines as a case study how the Directive has been implemented in Ireland.